Pengaruh Pesan Visual Pada Bungkus Rokok Terhadap Perilaku Merokok Mahasiswa (Studi Kuantitatif Deskriptif di Fakultas Hukum Ilmu Sosial Dan Humaniora Universitas Dharma Andalas) - Daniel Joshony Hamedeko; Indria Flowerina (CV. ITTC INDONESIA, 2025)
This study aims to analyze the influence of visual messages on cigarette packs on the smoking behavior of Dharma Andalas University students. Visual messages, such as health warning images, typography, color, and composition, are designed to increase awareness of the dangers of smoking and encourage behavioral changes in consumers. This study uses a descriptive quantitative approach with a survey method. Data were collected through a questionnaire involving 35 students of the Faculty of Law, Social Sciences, and Humanities who were selected using a purposive sampling technique. The results showed that visual elements on cigarette packs significantly influenced the cognitive, affective, and conative aspects of students' smoking behavior. From a cognitive perspective, visual messages increase understanding of the health risks of smoking. Affectively, warning images evoke fear or disgust that can encourage a reduction in cigarette consumption. Meanwhile, in the conative aspect, visual messages contribute to students' motivation to reduce smoking habits or quit completely. This study also found that effective visual communication design, such as the use of contrasting colors and bold typography, can strengthen the appeal of messages and influence behavior more significantly. These findings support the importance of government regulations, such as the obligation to include pictorial health warnings (PHW) on cigarette packs, in an effort to reduce the prevalence of smoking, especially in young age groups. This study provides practical contributions for policy makers and industry to improve the effectiveness of visual messages on tobacco products. In addition, the results can be used by educational institutions to improve education about the dangers of smoking, as well as by industry to improve compliance with tobacco control policies.